TINGKAT PENGETAHUAN PERPAJAKAN, KEPATUHAN DAN KETEGASAN SANKSI PERPAJAKAN TERHADAP PEMENUHAN KEWAJIBAN PERPAJAKAN - Remigius Jon Nalik; Suyanto Suyanto; Andri Wakista Aji (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to prove the effect of the level of tax knowledge, tax compliance and the firmness of tax sanctions on the fulfillment of the tax obligations of MSME entrepreneurs in the city of Yogyakarta. This study uses a quantitative descriptive method with primary data using a questionnaire. This study took a sample of 75 individual taxpayers who have SMEs in Yogyakarta City. The sampling technique used was random sampling. Data was collected by distributing questionnaires directly to respondents. The number of questionnaires that were processed were 75 questionnaires. Data were analyzed using multiple linear regression analysis. The results of this study indicate that the level of tax knowledge, tax compliance and the firmness of tax sanctions have a positive effect on fulfilling the tax obligations of MSME entrepreneurs in the city of Yogyakarta